1987
DOI: 10.1111/j.1365-2621.1987.tb14038.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles in Skin of Low Dose Irradiated Fresh Chicken

Abstract: Fresh chickens were irradiated with up to 1200 krad at &5"C. Volatile compounds from the skin and subcutaneous fat of these chickens, and from unirradiated controls, were analyzed by gas chromatography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 9 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Merritt et al (19) postulated that carbonyls are formed in irradiated meats due to the reactions of hydrocarbon radicals with molecular oxygen, which follows the same pathway as normal lipid oxidation. Hansen et al (11) reported that the amount of octane, 1-octene, hexanal, and nonane in irradiated chicken increased with the irradiation dose, but the volatile compounds were not unique products of irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Merritt et al (19) postulated that carbonyls are formed in irradiated meats due to the reactions of hydrocarbon radicals with molecular oxygen, which follows the same pathway as normal lipid oxidation. Hansen et al (11) reported that the amount of octane, 1-octene, hexanal, and nonane in irradiated chicken increased with the irradiation dose, but the volatile compounds were not unique products of irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…However, undesirable effects of food irradiation have included the development of off-flavors and odors. For chicken the threshold dose (2.5 kGy) is very low, and doses greater than 2.5 kGy might induce off-flavors while lower doses may not effectively inhibit growth of spoilage bacteria (Kahan and Howker, 1978;Urbain, 1983;Thayer, 1984;Hansen et al, 1987). Some treatments applied in combination with irradiation have been shown to exert a synergistic effect resulting in improved shelf-life of meats and meat products (Niemand et al, 1983;Licciardello et al, 1984;Barbut et al, 1987;Mattison et al, 1986;Ehioba et al, 1987).…”
Section: Introductionmentioning
confidence: 98%
“…Although we suggested nonane as a possible marker of vacuum packaged irradiated bacon (Singh et al, 1990), its use as a marker for other meats remains to be determined. For example, although it was reported to be present in irradiated but not in unirradiated vacuum packaged raw chicken (Merritt, 1984), Hansen et al (1987) detected a small amount of nonane in unirradiated raw chicken also, presumably in the presence of air. It has also been detected in unirradiated cooked chicken (Hobson-Frohock, 1970;Ramaswamy and Richards, 1982…”
Section: Resultsmentioning
confidence: 99%